CT scanning of capillary phenomena in bio-based materials - Couceiro, José; Sehlstedt-Persson, Margot; Hansson, Lars; Hagman, Olle; Sandberg, Dick (Luleå tekniska universitet, Träteknik, 2017)
X-ray computed tomography (CT) is a powerful tool for the non-destructive study of dynamic moisture processes in wood and other bio-based materials. In the CT facilities at Luleå University of Technology, it is possible to study wood-moisture relations such as water absorption, drying and related material deformation under a temperature- and humidity-controlled environment.An increase in the use of bio-based materials in building construction has led to an increased interest in capillary phenomena in these materials, because of an increasing number of moisture-related damage in timber and hybrid-timber buildings. This article shows some examples of how different bio-materials used in construction interact with liquid water over time. The overall purpose has been to develop the CT technique as a powerful tool for the determination and visualization of capillary flow that can be a base for modelling and an increased understanding of moisture flow in new bio-based building materials.Early-stage observation of the behaviour of different traditional and new bio-based building materials shows that CT scanning, combined with image processing, has a high potential to be used in performing non-destructive and non-contact tests that can help to increase the knowledge of water-material interactions and develop building materials with an optimized performance. 2018-01-23 (rokbeg);Konferensartikel i tidskrift